Educational Thinking from the Perspective of Children: Contemporary Comments on a Traditional Slogan - Gross, Stefan; Wehner, Ulrich (Journal of Education and Research, 2013)
Educational thinking has always been linked with a specific view on children. Although it is a matter of common knowledge, in closer examination the authors figure out that educational concepts deal surprisingly and imprecisely with their key subject. While progressive approaches made the term “From the perspective of the child” famous some 100 years ago, a brief analysis and the post-history enlightened contradictions, misunderstandings, and, in parts, fatal consequences of a careless or dogmatic use of the slogan. In their inconvenient meta-analysis, the authors vote for a consequent re-interpretation of the ideologically overloaded slogan by using it as a critical working-formula. Doing this, educational thinking from the perspective of children has massive consequences on the practical interaction between adults and children and the theoretical foundations of pedagogy. And it opens the door for a different kind of educational research with its objective to analyze the variety, heterogeneity and diversity of the life-world of children. DOI: http://dx.doi.org/10.3126/jer.v3i2.8191 Journal of Education and Research August 2013, Vol. 3, No. 2, pp. 1-14